Shear strength test on unsaturated soil using natural microscopic surface tension force / Basharudin Abdul Hadi - Abdul Hadi, Basharudin (Institute of Graduate Studies, UiTM, 2017)
The shallow infiltration influence slope failure is a complex soil mechanical behavior according to geotechnical engineers. This is because it is very difficult to obtain factor of safety less than unity according to conventional slope stability method for the shallow type of slope failure. The process involves the propagation of wetting front into the unsaturated soil zone. This involved the mechanics of saturated and unsaturated soil. The soils shear strength tests for saturated soils is well established and straight forward however the strength tests for unsaturated soils involves a very complex procedure. The procedure includes equalization, consolidation and shearing stages. The equalization process is a slow and tedious process where pore air and pore water pressure subjected to the partially saturated specimen are maintained and wait for the slow movement of the specimen water to travel through the ceramic disk attached at the Flood is a primary hazard affecting Malaysia, often responsible for loss of lives and a severe threat to infrastructure and environment. Activities in flood plain and catchment such as land clearing for other developments effort may increase the magnitude of a flood. The problem of flood management cannot be solved simply by providing more construction of dams and reservoirs. The adoption of a strategic approach is needed for planning and managing that flood management in any watershed. The evolution of distributed watershed models has been established for more accurate representation of the hydrological system by considering the spatial variability of model parameters and inputs. The research aims to evaluate the performance and hydrological response of the Soil Water Assessment Tool (SWAT) process-based model in tropical river basin using Malaysia soil data. This study was specific to the upper part of Langat River Basin (UPLRB) in the context of Greater Kuala Lumpur Plan in the southern region. The research also provides a streamflow prediction using the Artificial Neural Network (ANN) method as another tool for assessment. ArcSWAT2009.93.b, which is embedded in ArcGIS10, has been selected for this study, and the model requires comprehensive data on topography, soils, land use and daily weather data within a watershed. SWAT-CUP, which links SUFI-2 algorithm to SWAT models, has been utilized in the study for the calibration of SWAT models. There were two sets of algorithms in developing the UPLRB ANN model and every algorithm set consisted of model inputs data preparation, neural network 29 30 base of the specimen until the flow ceased..